Seroprevalence of Toxoplasma gondii in Pregnant Women Admitted to a State Hospital in Mersin, 2019 - Serpil Gonca; Mehmet Sami Serin; Sultan Halepliler; Sema Erden Ertürk (Türkiye Parazitoloji Dergisi, 2021)

(untitled)
Objective:This study aimed to retrospectively reveal the seroprevalence of Toxoplasma gondii (T. gondii) in pregnant women with routine pregnancy follow-up.Methods:Anti-T. gondii IgM-IgG antibody values of pregnant women aged 16-49 years, who had routine pregnancy follow-up in January-December 2019 were analysed retrospectively.Results:Of the 1.832 serum samples, in which the anti-T. gondii IgG test was studied, 28.7% were found to be positive, 70.4% were negative and 0.9% was found to be suspicious. For anti-T. gondii IgM, 0.7% of the 1.844 serum samples were evaluated as positive, 99.5% as negative and 0.1% as suspicious. The positivity rates was observed to increase as age decreases in anti-Toxoplasma IgM (r=0.144, p=0.001), and the positivity rates increase as the age increases in the anti-Toxoplasma IgG (r=0.061, p=0.001). In the nationality evaluation, the anti-T. gondii IgM and IgG positivity rates were observed to be higher in Syrian pregnant women compared to Turkish pregnant women.Conclusion:In our study, a significant portion of pregnant women were observed to be non-immune to the agent, and therefore informing these people about the protection methods from the parasite in order to prevent infection occurrence is important.